2014
DOI: 10.1038/leu.2014.158
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the PI3K/AKT pathway by microRNA-22 results in CLL B-cell proliferation

Abstract: Chronic lymphocytic leukemia (CLL) is characterized by accumulation of clonal B cells arrested in G0/G1 stages that coexist, in different proportions, with proliferative B cells. Understanding the crosstalk between the proliferative subsets and their milieu could provide clues on CLL biology. We previously identified one of these subpopulations in the peripheral blood from unmutated patients that appears to be a hallmark of a progressive disease. Aiming to characterize the molecular mechanism underlying this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 52 publications
5
56
0
Order By: Relevance
“…miR-22 is postulated to play an important role in CLL proliferation by targeting phosphatase and tensin homolog (PTEN), resulting in activation of the PI3K/AKT pathway. 47,48 In our study, miR-22 was highly expressed in CLL cells in the LN, lower in circulating CLL cells, and even lower in circulating Bcells from healthy controls. Ibrutinib resulted in a 3-fold decrease in miR-22 expression in patients' CLL cells, which was accompanied by a concomitant increase in PTEN transcripts.…”
Section: Discussionmentioning
confidence: 73%
“…miR-22 is postulated to play an important role in CLL proliferation by targeting phosphatase and tensin homolog (PTEN), resulting in activation of the PI3K/AKT pathway. 47,48 In our study, miR-22 was highly expressed in CLL cells in the LN, lower in circulating CLL cells, and even lower in circulating Bcells from healthy controls. Ibrutinib resulted in a 3-fold decrease in miR-22 expression in patients' CLL cells, which was accompanied by a concomitant increase in PTEN transcripts.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, factors that interfere with PI3K/Akt pathway such as PD-1 inhibit Th17 differentiation and induce Treg phenotype [137]. However, as the stimulation of PI3K/Akt pathway stimulates the proliferative capacity of leukemic cells [138], it seems that blocking this pathway in order to expansion of Th17 cells may be rational. However, inhibition of this pathway may induce apoptosis in B-CLL cells [139].…”
Section: Future Science Groupmentioning
confidence: 98%
“…Accumulating amounts of evidence suggest that miR-22-3p partcipates mainly in cell growth and differentiation. Previous studies have shown that miR-22-3p can promote CLL-B cell and cardiomyocytes proliferation [26,27]; however, in most carcinomas, including breast cancer [28], gastric carcinoma [29], medulloblastomas [30] and liver cancer [31], miR-22-3p suppressed cancer cell proliferation. Thus the biological functions of miR-22-3p in HASMCs require further study.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%